Visualization skills among Universiti Teknologi Malaysia student - Ali, Dayana Farzeeha (2014)
Visualization skills are very important in engineering field and it is positively correlated with achievement in engineering disciplines. Therefore, this preliminary study was carried out to study the levels of visualization skills among engineering students in Universiti Teknologi Malaysia (UTM) Skudai. 730 respondents were involved in this study. They were students from thirteen faculties in this campus. The respondents of this study were first year until fourth year students. This quantitative study was analyzed using descriptive method. The instruments in this study were biographical data sheet and short version of visualization standard tests. The finding of this preliminary study reveals that UTM students possess moderately high skill in visualization. Thus, suitable teaching approach should be taking into consideration in order to provide the right technique to enhance students' visualization skills.